Topography of the Young Galactic Disk: Spatial and Kinematic Patterns of Clustered Star Formation in the Solar Neighborhood - Alfaro, Emilio J.; Jiménez, Manuel; Sánchez-Gil, M. Carmen; Sánchez, Néstor; González, Marta; Apellániz, Jesús Maíz (The Astrophysical journal, 2022)
The accuracy in determining the spatial-kinematical parameters of open clusters makes them ideal tracers of the Galactic structure. Young open clusters (YOCs) are the main representatives of the clustered star formation mode, which identifies how most of the stars in the Galaxy form. We apply the Kriging technique to a sample of Gaia YOCs within a 3.5 kpc radius around the Sun and log(age) ≤ 7.5, as the age in years, to obtain Z ( X , Y ) and V Z ( X , Y ) maps. Previous work by Alfaro et al. has shown that Kriging can provide reliable results even with small data samples ( N ∼ 100). We approach the 3D spatial and vertical velocity field structure of the Galactic disk defined by YOCs and analyze the hierarchy of the stellar cluster formation, which shows a rich hierarchical structure, displaying complexes embedded within each other. We discuss the fundamental characteristics of the methodology used to perform the mapping and point out the main results obtained in phenomenological terms. Both the 3D spatial distribution and the vertical velocity field reveal a complex disk structure with a high degree of substructures. Their analysis provides clues about the main physical mechanisms that shape the phase space of the clustered star formation in this Galactic area. Warp, corrugations, and high local deviations in Z and V Z appear to be intimately connected, in a single but intricate scenario.